Rapid Geriatric Assessment Using Mobile App in Primary Care: Prevalence of Geriatric Syndromes and Review of Its Feasibility - Merchant, Reshma Aziz; Hui, Richard Jor Yeong; Kwek, Sing Cheer; Sundram, Meena; Tay, Arthur; Jayasundram, Jerome; Chen, Matthew Zhixuan; Ng, Shu Ee; Tan, Li Feng; Morley, John E. (Frontiers in Medicine, 2020)
With aging population and consequent increase in associated prevalence of frailty, dementia and multimorbidity, primary care physicians will be overwhelmed with the complexity of the psychosocial and clinical presentation. Geriatric syndromes including frailty, sarcopenia, cognitive impairment and anorexia of aging either in isolation or combination is associated with increased risk of adverse outcomes and if recognised early, and appropriately managed, will lead to decreased disability. Primary care practices are often located in residential setting, and are in ideal position to incorporate preventive screening and geriatric assessment with personalised management. However, primary care physicians lack the time, multidisciplinary resources or skills to conduct geriatric assessment, and the limited numbers of geriatricians worldwide further complicates the matter. There is no one effective strategy to implement geriatric assessment in primary care which is rapid, cost effective and do not require geriatricians. Rapid Geriatric Assessment (RGA) takes less than 5 minutes to complete. It screens for frailty, sarcopenia, anorexia of aging and cognition with assisted management pathway without the need of a geriatrician. We developed RGA iPad application for screening with assisted management in two primary care practices, and explored the feasibility, overall prevalence of frailty, sarcopenia and anorexia of aging. The assessment was conducted by trained nurses and coordinators. Amongst 2589 older patients ≥ 65 years old, prevalence of frailty was 5.9%, pre-frail 31.2% and robust 62.9%. Fatigue was present in 17.8% , and amongst them, the prevalence of undiagnosed depression as assessed by PHQ-9 was 76.4% and 13.5% of total. The prevalence of sarcopenia was 15.4% and 13.9% experienced at least one fall in the past year. Anorexia of aging was prevalent in 10.9%. The time taken to do the assessment with defined algorithm was on average five minutes or less per patient and 96% managed to complete the assessment prior to seeing their doctor in the same session. The RGA app is a rapid and feasible tool to be used by any healthcare professionals in primary care for identification of geriatric syndrome with assisted management.